2006
DOI: 10.4049/jimmunol.177.8.5169
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-Dependent Kinase Inhibitor p27kip1 Is Required for Transplantation Tolerance Induced by Costimulatory Blockade

Abstract: The cyclin-dependent kinase (CDK) inhibitor p27kip1 is an important negative regulator of the cell cycle that sets a threshold for mitogenic signals in T lymphocytes, and is required for T cell anergy in vitro. To determine whether p27kip1 is required for tolerance in vivo, we performed cardiac allograft transplantation under conditions of combined CD28/CD40L costimulatory blockade. Although this treatment induced long-term allograft survival in wild-type recipients, costimulatory blockade was no longer suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…CDK1 is the major driver of cell-cycle progression, CDK2 has been shown to be essential for optimal T cell activation and differentiation, and the CDK9 target MCL1 is required for the survival of activated T cells (75,76). Inhibition of CDK2 through p27 Kip1 , a cell-intrinsic inhibitor of CDKs that is expressed in T cells, has been linked to PD1 and CTLA4 signaling, T cell peripheral tolerance, and CD8 T cell memory, highlighting the importance of CDKs in the maintenance of an active immune response (75,(77)(78)(79)). Yet we observed enhancement of antitumor immunity in our studies and no apparent drop in the number of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 is the major driver of cell-cycle progression, CDK2 has been shown to be essential for optimal T cell activation and differentiation, and the CDK9 target MCL1 is required for the survival of activated T cells (75,76). Inhibition of CDK2 through p27 Kip1 , a cell-intrinsic inhibitor of CDKs that is expressed in T cells, has been linked to PD1 and CTLA4 signaling, T cell peripheral tolerance, and CD8 T cell memory, highlighting the importance of CDKs in the maintenance of an active immune response (75,(77)(78)(79)). Yet we observed enhancement of antitumor immunity in our studies and no apparent drop in the number of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of p27 kip1 has been shown to induce anergy (20), whereas CD4 ϩ T cells that lack p27 kip1 are resistant to anergy induced by a costimulatory blockade in vitro (19). Moreover, p27 kip1 -deficient mice are unable to develop donor-specific tolerance to cardiac allografts in response to a costimulatory blockade in vivo (21). Some modes of anergy induction do not require p27 kip1 .…”
Section: Signals From Il-2r Are Required For T Cells To Escape Anergymentioning
confidence: 99%
“…These suggest that p27 (kip1) plays a complex and important role in the regulation of cell division and effector function development in CD4 + T cells (65)(66)(67). Besides this, it has been shown that cell cycle re-entry of quiescent T cells is dependent upon CDK2, and inhibition of CDK2 by p27 (kip1) is the principal constraint on S-phase entry in T cells.…”
Section: Cell Cycle Progressionmentioning
confidence: 99%